Fishes from the Parque Nacional do Pantanal Matogrossense, upper Paraguai River basin, Brazil - Polaz, Carla Natacha Marcolino; Melo, Bruno F. [UNESP]; Britzke, Ricardo [UNESP]; de Resende, Emiko Kawakami; de Arruda Machado, Francisco; de Lima, José Augusto Ferraz; Petrere, Miguel (Pensoft Publishers, 2014)
The Pantanal Biosphere Reserve contains one of the highest concentration of animal species in the Neotropics, including about 300 fish species living in diverse environments associated with wetlands in the upper Paraguai River basin. This biome spans portions of Bolivia, Brazil and Paraguay and includes the Parque Nacional do Pantanal Matogrossense (PNPM), a region of the Pantanal which has been assigned as high conservation priority in Brazil. This study reports the results of an ichthyological survey within the PNPM, where samples were taken at 12 sites during the dry season in 2001, 2010 and 2011. We record 182 species representing three classes, 10 orders and 41 fish families. We report the first occurrence of the genus Anchoviella (order Clupeiformes), in the La Plata basin. This survey will provide information for future studies concerning conservation and management plans for the PNPM as well as for the Pantanal, which is one of the largest permanent wetland areas in the world and among the most unique and important South American biomes. © 2014 Check List and Authors.